2020
DOI: 10.1088/1361-6528/ab978b
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable electronic and optical properties of BlueP/MoS2 van der Waals heterostructure by external strain: a first-principles study

Abstract: Blue phosphorene (BlueP) has been widely researched recently as a potential material for novel photocatalytic and electronic devices. In this letter, due to its similar in-plane hexagonal lattice structure to MoS2, BlueP/MoS2 van der Waals heterostructures were built in six configurations. The II-stacking configuration was the most stable due to the lowest binding energy obtained from the calculation results. Furthermore, by controlling the external vertical strain, the geometry structures were optimized and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…While the electronic states above the Fermi level are contributed by Si ( s orbitals) and S atoms ( p orbitals). These results again confirm the type II band alignment of the AB-2 SiS 2 /WSe 2 hetero-bilayer, which can effectively separate the photogenerated holes and electrons [ 46 , 47 , 48 , 49 ]. Owing to the narrower band gap (0.154 and 0.738 eV obtained by GGA-PBE and HSE06, respectively), the electrons are more susceptible to being excited from VBM to CBM when the SiS 2 /WSe 2 heterostructure is exposed to light [ 50 ].…”
Section: Resultssupporting
confidence: 69%
“…While the electronic states above the Fermi level are contributed by Si ( s orbitals) and S atoms ( p orbitals). These results again confirm the type II band alignment of the AB-2 SiS 2 /WSe 2 hetero-bilayer, which can effectively separate the photogenerated holes and electrons [ 46 , 47 , 48 , 49 ]. Owing to the narrower band gap (0.154 and 0.738 eV obtained by GGA-PBE and HSE06, respectively), the electrons are more susceptible to being excited from VBM to CBM when the SiS 2 /WSe 2 heterostructure is exposed to light [ 50 ].…”
Section: Resultssupporting
confidence: 69%
“…Moreover, the optical absorption coefficient of MoSSe/graphene vdWHs have been improved through its natural characteristics of dipole and layer numbers [119]. Meanwhile, the vdWHs possess intensive optical absorption compared with that of corresponding monolayers [120,121]. These findings have revealed that the 2D vdWHs are prospective candidates in the application of photodetectors.…”
Section: Photodetectorsmentioning
confidence: 97%
“…Many BP/XT 2 (X = Mo, W; T = S, Se, Te) heterostructures with type-II band alignments would be prospective as spin-filter devices [36]. BlueP/MoS 2 has been considered the next generation of photovoltaic devices and water-splitting materials due to its wide optical response range and good light absorption ability [37]. In addition to the theoretical research such as that mentioned above, there have been experimental studies on bilayer vdW heterostructures to explore their practical prospects.…”
Section: Introductionmentioning
confidence: 99%